Death in paradise. Season twelve [videorecording (DVD)] - Thorogood, Robert (BBC, 2023)
The sun-soaked, smash-hit whodunnit returns for more murder mysteries with a light touch and a warm heart. DI Neville Parker has more crimes to solve on the blissful island of Saint Marie, kicking off with the mysterious death of a celebrity astronomer. And on a quiet hillside on the island, a bunch of Preppers is digging in for the apocalypse when one of them is killed. There's also a baffling killing on a boat, a famous singer who finds herself under suspicion, a shocking murder at a wedding, and a simple domestic murder, that turns out to be Neville's greatest-ever challenge. Includes 2022 Christmas Special.